1999
DOI: 10.1348/096317999166518
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unemployment on mental health

Abstract: Sixteen recent longitudinal studies are examined for evidence relevant to the claim that a change to one's employment status affects one's mental health. Although there were limitations to the set of studies examined, most of the studies supported this claimed relationship. Examination was then made of the size of this effect. In carrying out this examination, the set of study results were divided into two categories: (a) those addressing the question of the extent to which gaining employment impacts on mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
305
1
29

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(351 citation statements)
references
References 36 publications
16
305
1
29
Order By: Relevance
“…Unemployment and job insecurity are two of the principal mediating factors that lead temporary employment to be negatively associated with health Caroli and Godard, 2013;Virtanen et al, 2005). Unemployment has been found to deteriorate mental health (Murphy and Athanasou, 1999) due to the financial difficulties or extreme psychological strain that it triggers (Pearlin, 1989). Moreover, it has been argued and demonstrated that job insecurity has negative effects on physical and psychological well-being (Bohle et al, 2001;Waenerlund et al, 2011), self-rated health, psychiatric morbidity or long standing illness (Ferrie et al, 2005).…”
Section: Pathways Between Temporary Work and Healthmentioning
confidence: 99%
“…Unemployment and job insecurity are two of the principal mediating factors that lead temporary employment to be negatively associated with health Caroli and Godard, 2013;Virtanen et al, 2005). Unemployment has been found to deteriorate mental health (Murphy and Athanasou, 1999) due to the financial difficulties or extreme psychological strain that it triggers (Pearlin, 1989). Moreover, it has been argued and demonstrated that job insecurity has negative effects on physical and psychological well-being (Bohle et al, 2001;Waenerlund et al, 2011), self-rated health, psychiatric morbidity or long standing illness (Ferrie et al, 2005).…”
Section: Pathways Between Temporary Work and Healthmentioning
confidence: 99%
“…A growing body of social and health sciences literature has focused on the negative consequences of insecure employment on individuals' occupational prospects; their private, family, and, social lives; and their wellbeing. The existing studies which have examined mental health outcomes have tended to focus on the risk of unemployment or the experience of job loss (Murphy & Athanasou, 1999;McKee-Ryan, Song, Wanberg, & Kinicki, 2005). A recent extensive review of the empirical literature on insecure unemployment (Paul & Moser, 2009) showed that on average people who were unemployed experienced more distress than people who had a job, although the strength of the association depended on the measure of mental health used.…”
mentioning
confidence: 99%
“…Indeed, there is ample evidence from previous economic crises showing that people affected by unemployment, impoverishment and family problems have a significantly higher risk of mental health problems such as major depression, suicide and problems related to alcohol consumption and psychoactive substances, than unaffected people (Blakely et al 2003;Chang et al 2009;Dee 2001;Dooley et al 1994;Dorling 2009;Fryers et al 2005;Gunnell et al 1999;Lewis and Sloggett 1998;Mathers and Schofield 1998;McKee-Ryan et al 2005;Murphy and Athanasou 1999).…”
Section: Hospitalisation Episode Rate Variationmentioning
confidence: 99%
“…Factors like household indebtedness, unemployment and impoverishment are potentiated in times of economic crisis and play a crucial role in the development of mental illnesses (Jenkins et al 2008;Reading and Reynolds 2001;Skapinakis et al 2006;Taylor et al 2007; WHO 2011) predisposing people to a higher risk of mental health problems such as major depression, alcohol consumption and suicide (Dee 2001;Dooley et al 1994;Dorling 2009;Lewis and Sloggett 1998;Mathers and Schofield 1998;McKee-Ryan et al 2005;Murphy and Athanasou 1999).…”
Section: Introductionmentioning
confidence: 99%